Rezeki dalam Al-Qur’an (Analisis Perbandingan Tafsir Al-Qurṭubĭ dan Tafsir Al-Azhar) - Febriyanti, Ika; Purnama Sari, Putri; Rahma Yuniarti P, Talitha (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
This study aims to understand the concept of sustenance in the Islamic context, particularly through identifying similarities and differences in the Qur’anic interpretation of sustenance in the Surah as-Saba and al-Baqarah. The research method used is library research focusing on Hamka’s Tafsir Al-Azhar and Imam Al-Qurthubi’s exegetical work. The results of the research show that Allah SWT is the provider of sustenance who determines the amount and method of obtaining it. Even though Allah determines sustenance, humans still need to try to get it. In addition, Islam teaches the importance of sharing sustenance with others and helping people in need. This study also emphasizes that Islam is not only related to material aspects, but also includes various other aspects of life. In creative synthesis, this study presents the results of the analysis of the two elaborational interpretation as a more comprehensive understanding of sustenance in the Islamic context. The results of this study can also provide deeper insight into how Muslims can be grateful, work hard, share, and support good deeds and obedience to Allah SWT in seeking blessed sustenance.